A new strut model for solid masonry infills in steel frames. (15th March 2017) - Yekrangnia, Mohammad; Mohammadi, Majid
Highlights: A single model is proposed in this paper to consider both local and global effects of infill panels on structures. The model can also consider nonlinear behavior of infills accurately. The proposed three-strut model considers strut width, angle and contact length as variables by parameters including relative stiffness of frame to infill wall, friction angle between masonry blocks and infilled frame height to length ratio. Abstract: This paper presents in-depth results of a proposed strut model for masonry infill walls in moment-resisting steel frames. The proposed model is based on the results of calibrated finite element analyses and hence gives realistic representation of infilled frames behavior. Comparisons are made between the results of the proposed model and other existing strut models; ASCE beam-to-beam, ASCE column-to-column and El-Dakhakhni. The results prove that considerable improvement has been made in capturing the internal forces of the frame members and force-displacement diagram of infilled frames by the new model compared to the existing models. Robustness of the proposed model is also confirmed in predicting performance of several experimental results of infill walls in steel frames. The model can be observed in the following figure: a P = 0.001 a M ( 6 θ + 7.5 α p ) θ and α p in degrees L ceff - p = 0.006 h ( θ + α p - 10 λ l h ) θ and α p in degrees α ≅ tan - 1 1 μ α p = α - λ l h α p and α in degrees a M is Mainstone proposed strut model and μ is coefficient of friction between bricks of the wall.